Penerapan Metode Behaviorally Anchored Rating Scale Dalam Penilaian Kinerja Guru SMK Pab 8 Sampali Berbasis Web - Ginting, Erwin; Wahyuni, Linda; Fahrozi, Wirhan; Adhar, Deni; Harahap, Ahir Yugo Nugroho (LPPM STIKOM Tunas Bangsa, 2024)
A teacher is the spearhead of educational progress, not only at the elementary, middle and high school levels. Teacher expertise and performance are important things that really need to be observed and evaluated, so that the learning provided to students can run well. As computer/internet-based technology develops, it is very possible to implement teacher performance assessments using an online/online application so that it is easier to evaluate and assess, in formulating teacher assessments requires a benchmark/ measurement in this case the Behaviorally Anchored Rating Scale method. which is very appropriate to be applied in assessing teacher performance at the SMK PAB 8 Sampali